2007
DOI: 10.1080/14756360701425238
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative structure-activity relationships studies of antioxidant hexahydropyridoindoles and flavonoid derivatives

Abstract: In order to predict the antioxidant activity of 22 pinoline derivatives (1,2,3,4-tetrahydro-beta-carbolines), two dimensional quantitative-structure activity relationships (2D-QSAR) analysis of 19 hexahydropiridoindoles and 12 flavonoids was realized. Five statistically significant models were obtained from randomly constituted training sets (21 compounds) and subsquently validated with the corresponding test sets (10 compounds). Antioxidant activity (pIC50) was correlated with 5 molecular descriptors calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…Quantitative structure-activity relation (QSAR) correlating the activities with the structural features or descriptors of the compounds were also developed to understand the importance of certain structural features on their antioxidant activities. Some of the earlier researcher too explored the quantitative relationship (QSAR) between the antioxidant activities and the physiochemical properties (Farkas et al, 2004;Durand et al, 2007).…”
Section: Superoxide (Omentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative structure-activity relation (QSAR) correlating the activities with the structural features or descriptors of the compounds were also developed to understand the importance of certain structural features on their antioxidant activities. Some of the earlier researcher too explored the quantitative relationship (QSAR) between the antioxidant activities and the physiochemical properties (Farkas et al, 2004;Durand et al, 2007).…”
Section: Superoxide (Omentioning
confidence: 99%
“…It is mentioned before that increase in aqueous solubility will also result in improved antioxidant activity. Durand et al (2007) also found the contribution of functional groups, such as like number of tertiary carbon atoms and number of aliphatic ketones towards antioxidant activity.…”
Section: Reducing Power Activitymentioning
confidence: 99%
“…The calculation of the topological, the molecular, and the functional group descriptors was carried out with Dragon 2.1 program [22] following the methodology described in a previous study [11]. The resulting descriptor values were introduced in Equation 1, (a QSAR equation previously validated for 19 hexahydropyridoindoles and 12 flavonoids), to predict the antioxidant power of compounds 2, 3 and 4.…”
Section: Selection Of the Descriptorsmentioning
confidence: 99%
“…Using the low-density lipoprotein oxidation model, we have previously described a QSAR analysis of structural analogues of melatonin [6,7], and have subsequently characterized the antioxidant activity of azaheterocycles from the tryptamine series [8][9][10], proposing a model with 5 molecular descriptors [11]. Due to their structures, lactams 2 and 3 have called our attention as candidates for new anti-oxidative agents.…”
Section: Introductionmentioning
confidence: 99%
“…The division was made to cover the entire antioxidant activity scale [29,30] and the samples included in the training set were randomly selected within each group [31]. The goodness of fit of the models was evaluated using r 2 , s, , and F. The predictive stability and robustness of the model was first verified by internal cross-validation calculating the following parameters: Q 2 LOO , permutation test of SIMCA-p software and RMSE (training set) [27,28,32].…”
mentioning
confidence: 99%